Otimização dos recursos energéticos no distrito de irrigação do Platô de Neópolis - Siqueira, Carlos Henrique de Goes (2007)
The present work had as a experimental area the project of irrigated fruit crop District of Irrigation Platô de Neópolis, that is located at the east of the State of Sergipe, in the right margin of the river S. Francisco, including part of the municipal districts of Neópolis, Pacatuba, Japoatã and Santana do São Francisco, distant about 100 km of the capital Aracaju, during the period of july/2005 to october/2006. It had as objective evaluates the acting of the transport system and distribution of water used in the District of Irrigation Platô de Neópolis, being verified the use of the existent equipments is in accordance with the water crops requirements, and to propose an operation plan for those equipments that it optimizes the use of the electric power. The water requirements were certain starting from the indirect estimate of the reference evapotranspiration for the method of Penman-Montheith, considered pattern since 1998 and recommended by FAO - Food and Agricultural Organization of the United Nations. The climatic elements (temperature, relative humidity of the air, heatstroke, speed of the wind, radiation, among other) used in the model were obtained in the conventional station of INMET-National Institute of Meteorology, located in the city of Propriá/SE. Known the volume of water was calculated the pumping work necessary for his distribution and the cost of the associated electric power, taking into account the local tariffs and the legislation of the pertinent electric section to the irrigation activity. The savings obtained with the new operation plan can bring sustainability to the District of Irrigation Platô of Neópolis and they be reverted in the expansion of the planted area, in way to influence positively the socioeconomics conditions in the municipal districts of the area.